ChemInform Abstract: Photo‐Induced Formation of Cyclopropanols from α‐Ketoamides via γ‐C—H Bond Activation. Issue 9 (February 2016) - Ota, Eisuke; Mikame, Yu; Hirai, Go; Koshino, Hiroyuki; Nishiyama, Shigeru; Sodeoka, Mikiko
Abstract: α‐Ketoamides of type (I) and (VI) undergo cyclization under irradiation with blue LED‐light to form cyclopropanols through a diradical precursor generated by H‐atom abstraction by the amide group.